The results of adding immunotherapy to chemotherapy in patients with small cell lung cancer: Registurk-Lung study-Real-world data - Cil, Timucin; Hacibekiroglu, Ilhan; Uncu, Dogan; Isikdogan, Abdurrahman; Ates, Ozturk; Sendur, Mehmet Ali Nahit; Altinbas, Mustafa (Lippincott Williams & Wilkins, 2024)
[Abstract Not Available]
Special Clinical Science Symposia -- MAY 29-29, 2024 -- ELECTR NETWORK